2018
DOI: 10.1017/s2045796018000409
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of parents of mentally-ill children: a systematic review and meta-analysis

Abstract: The compromised QOL of parents of mentally-ill children needs to be considered and addressed by health professionals who are in contact with them. The paper provides insights into existing research gaps and suggests improvements for subsequent work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 54 publications
5
35
0
2
Order By: Relevance
“…Lower scores of QOL of parents having a child diagnosed with ADHD were noticed in many studies. 12 In this study, significant improvement was noticed in different QOL domains, especially in the social domain after the intervention (table 1). The lower scores in social domain may be explained by the bullying and the stigma that usually follow psychological disorders from the community.…”
Section: Discussionsupporting
confidence: 50%
“…Lower scores of QOL of parents having a child diagnosed with ADHD were noticed in many studies. 12 In this study, significant improvement was noticed in different QOL domains, especially in the social domain after the intervention (table 1). The lower scores in social domain may be explained by the bullying and the stigma that usually follow psychological disorders from the community.…”
Section: Discussionsupporting
confidence: 50%
“…ADHD in children may also affect the well-being of their parents. Several studies have shown that parents of children with ADHD experience more parenting stress than parents of typically developing children (Herrerias et al, 2001;Brandt-Dominicus, 2005;Poulton et al, 2013;Dey et al, 2018) perhaps resulting from the increased demands of caretaking, economical costs of medical care, role dissatisfaction, increased levels of parental frustration, marital discord, or divorce (Laugesen et al, 2016). The parenting stress level that parents experience is directly related to the number of ADHD symptoms in their children, according to a range of studies (Deault, 2010;Graziano et al, 2011;Haack et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Left untreated, such symptoms lead to untoward functional consequences in young people, including worse academic outcomes ( 9 , 10 , 11 ). Both ADHD symptoms and sleep problems can produce profound disruption in daily life and impact negatively quality of life of both the child and the family ( 12 , 13 , 14 ). ADHD symptoms such as hyperactivity can lead to longer sleep onset latency, more night awakening, and lower sleep quality ( 15 ), but disrupted sleep can also impair daytime attention, overlapping with the core symptoms of ADHD ( 16 ).…”
mentioning
confidence: 99%